Answer:
The first derivative of [tex]y = \sinh^{-1} (x^{2}+1)[/tex] is [tex]y' = \frac{2\cdot x}{\sqrt{x^{2}+2\cdot x +2}}[/tex].
Step-by-step explanation:
We proceed to find the first derivative of [tex]y = \sinh^{-1} (x^{2}+1)[/tex] by explicit differentiation and rule of chain:
[tex]y = \sinh^{-1} (x^{2}+1)[/tex]
[tex]y' = \frac{2\cdot x}{\sqrt{(x^{2}+1)^{2}+1}}[/tex]
[tex]y' = \frac{2\cdot x}{\sqrt{x^{2}+2\cdot x +2}}[/tex]
The first derivative of [tex]y = \sinh^{-1} (x^{2}+1)[/tex] is [tex]y' = \frac{2\cdot x}{\sqrt{x^{2}+2\cdot x +2}}[/tex].